UJI EFEKTIVITAS EKSTRAK ETANOL DAUN GAGATAN HARIMAU (Vitis gracilisWall) TERHADAP PENAMBAH STAMINA PADA MENCIT JANTAN - Syafitri, Anggun; Sianipar, Masria Phetheresia; Agustina, Putri (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Stamina is the ability of human endurance to withstand fatigue within a certain time limit, where activities are carried out with high intensity and always use energy that can be treated with traditional medicine derived from plants. One example of plants that can increase stamina is tiger gagatan leaves which contain flavonoids that can increase the motor activity of mice by inhibiting the absorption of calcium ions entering the sarcoplasmic reticulum after that with the obstacle causing high calcium ion levels in sarcoplasm and containing tonic effects. The purpose of the study was to determine the effect of giving tiger gagatan leaf extract in increasing stamina compared to caffeine. This research was conducted by experimental method, samples were extracted maceration using 96% ethanol solvent and concentrated with a rotary evaporator. Using 25 mice and divided into 5 groups. The control group was negative CMC-Na 0.5%, the control group positive for caffeine 0.13mg/kgBB, EDGH with a dose of 50mg/kgBB, EDGH with a dose of 100mg/kgBB, EDGH with a dose of 200mg/kgBB. Then observed the endurance time of mouse stamina and calculated the average physical endurance time of mice by swimming method. From the results of the study that the EDGH dose of 200mg/kgBB had optimal effectiveness close to the positive control group with swimming endurance time of 52.18 minutes, while EDGH with a dose of 100mg / kggBB showed a physical endurance time of mice of 49.07 minutes, and EDGH 50mg / kg BB showed a physical endurance time of mice of 48.24 minutes. So it can be concluded that tiger gagatan leaf extract at a dose of 200mg/kgBB has an effectiveness equivalent to caffeine in increasing stamina against male white mice.